KUAT TEKAN DAN KUAT TARIK-BELAH BETON AKIBAT PENGGUNAAN AGREGAT KASAR PELLET PLASTIK POLYPROPYLENE TEREPHTALATE - Jalali, Nur Aisyah; Erdiansa, Andi (FORUM BANGUNAN, 2013)
Plastics which are classified as inorganic wastes take a long time to decompose. The amount of plastic that is continuously increasing requires serious treatment to avoid its environment problem. It is therefore important to minimize the discharge of waste with reusing and recycling, so that the disposed waste will be fewer. This research aims to find the effect of plastic pellets as a coarse aggregate to the weight-volume, compressive strength, and split tensile strength of concrete compared with normal concrete (crushed stone as the coarse aggregate), and to determine classification based on the weight-volume and compressive strength of concrete. The results of the research showed that the higher levels of plastic pellets in concrete, the lower the weight-volume, compressive strength, and split tensile strength of concrete, where a decline to normal concrete. According to SNI 03-3449-2002, concrete with 60% and 80% pellets levels are not classified as lightweight concrete, whereas concrete with 100% pellets levels are classified as structural lightweight concrete because its weight-volume is less than 1850 kg/m3. The results of compressive strength test showed that concrete with 60%, 80%, and 100% pellets levels are categorized as structural lightweight concrete because its compressive strength is more than 17,3 MPa, whereas according to SNI 03-3449-2002 are categorized as structural lightweight concrete. Keywords: pellet, split tensile strength, lightweight concrete